Preparation of Nanofluids of Some Iron Compounds from Industrial Waste FeSO4+7H2O as Precursor for NOx Reduction - Kim, D.C.; Kim, J.H.; Woo, J.K.; Nho, N.S.; Shin, D.H.; Kaushik, R.D. (Asian Journal of Chemistry, 2010)
Keeping in view the reported NOx reduction potential of solid powders of iron containing compounds like FeO, Fe2O3 and Fe3O4, the new, simpler and cost effective methods for preparation of nanofluids of Fe(OH)3, Fe(OH)2 and Fe3O4 in diesel have been developed and presented. Fe(OH)3 and Fe(OH)2 are expected to convert into FeO, Fe2O3 at furnace temperature of about 1500 ºC in combustion facilities and than act as NOx reduction agents. These nanofluids shall have advantage due to increased surface area of particles leading to better surface reactions required for NOx reduction. The industrial waste FeSO4·7H2O has been used for the first time as the starting material for the same for making the methods cost effective. The results of analysis for iron content and particle size determination have also been reported.